Inovação no Sector dos Serviços: Uma Nova Área de Investigação - Sarkar, Soumodip; Carvalho, Luísa (Tourism & Management Studies, 2006)
One of the biggest challenges facing firms today is the need to innovate. However, innovation is poorly understood, especially in the case of service sector. This paper aims to appoint the biggest differences between manufacturing and service sectors, to define what is innovation in services and which variables and models are best suited to study innovation in services.